2016
DOI: 10.1007/s00223-016-0202-y
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Properties of an Array of –NH2-Modified Substrates for the Induction of a Mature Osteoblast/Osteocyte Phenotype from a Primary Human Osteoblast Population Using Controlled Nanotopography and Surface Chemistry

Abstract: Accelerating the integration of a joint replacement or the healing of a bone fracture, particularly a complicated non-union fracture, would improve patient welfare and decrease healthcare costs. Currently, an autologous bone graft is the gold standard method for the treatment of complicated non-union fractures, but it is not always possible to harvest such a graft. A proactive highly inductive so-called smart material approach is pertinent in these cases. In this study, the surface chemistry of a previously ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Parallel studies have proven that the CL11 substrates that were highly osteoinductive (ability to induce osteogenesis in MSCs) did not display significantly enhanced osteoconductive (ability to enhance the function of osteoblasts) behavior in vitro . Instead the shorter chain silanes supported osteoblast clustering and resulted in an upregulation of osteoblast activity and production of calcified matrices . This proves that different combinations of submicron material stimuli are required to increase the efficiency of different cell phenotypes in vitro .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Parallel studies have proven that the CL11 substrates that were highly osteoinductive (ability to induce osteogenesis in MSCs) did not display significantly enhanced osteoconductive (ability to enhance the function of osteoblasts) behavior in vitro . Instead the shorter chain silanes supported osteoblast clustering and resulted in an upregulation of osteoblast activity and production of calcified matrices . This proves that different combinations of submicron material stimuli are required to increase the efficiency of different cell phenotypes in vitro .…”
Section: Discussionmentioning
confidence: 85%
“…The enhanced level of osteogenic cell maturity and production of an organized osteogenic rich extra cellular matrix was only observed on the CL11 modified surfaces. It is essential to reiterate that the observed cellular response on the CL11 surfaces was homogenous across the entirety of the surface, therefore, proving that modification with CL11 –NH 2 silanes is an effective mechanism to produce cost effective osteoinductive coatings on different base substrates over a large surface area …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that changing the chain length of silane changes the surface topography of a substrate, via deposition of amine groups, therefore controlling initial cell adhesion and influencing cellular differentiation 9 . Silane chain length has been previously shown to control osteo‐induced differentiation of mesenchymal stem cells, and a similar effect was hypothesized for neuronal cell differentiation 10 .…”
Section: Discussionmentioning
confidence: 94%
“…Previous work has demonstrated enrichment of surfaces with chemical reactive groups including amines, hydroxyl, and carboxyl 5 . Silane modification can mimic the ECM by changing surface nano‐topography, and substrate chemistry, providing a biological surface to enhance initial cell attachment and maintain proliferation 9 . Silane chain length has been shown to influence deposition of the chemical reactive group at submicron scale, and influence cell adhesion and differentiation due to topographic profile 9 …”
Section: Introductionmentioning
confidence: 99%
“…Understanding surface chemistry of biomaterials becomes increasingly important for progress of regenerative medicine [1][2][3] as the initial interaction of biomaterials with cells is determined by parameters that define surface chemistry including wetting behavior, surface charge, homogeneity, functional groups, and surface topography. [4][5][6] Transplant materials usually need surface modifications to increase biocompatibility and to preserve the engineered function of the implant.…”
Section: Introductionmentioning
confidence: 99%